2022
DOI: 10.1021/acsanm.1c03759
|View full text |Cite
|
Sign up to set email alerts
|

Aminated Polyacrylonitrile Nanofiber Membranes for the Removal of Organic Dyes

Abstract: Adsorption is a promising technique for the effective removal of dyes from dyeing wastewater resulting from the paper, textile, and leather industries. Herein, we report a facile strategy for preparing adsorption membrane-based aminated ultrathin polyacrylonitrile (UPAN-N) nanofibers to effectively remove the synthetic dyes from wastewater. The UPAN-N nanofibers were synthesized using a mixed solution electrospinning procedure, followed by triethylenetetramine modification. After the amino modification, the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The electrospinnun polymer nanofiber membranes have a high aspect ratio and surface adsorption energy, providing an effective adsorbent material that can be regenerated without secondary contamination [ 230 , 231 , 232 , 233 ]. Recently, Zhao et al reported a simple strategy to fabricate amine-functionalized ultrathin polyacrylonitrile nanofiber of 100 nm diameter using a mixed solution electrospinning procedure, to efficiently remove organic dyes from aqueous media [ 234 ]. The ultrathin polyacrylonitrile nanofiber membrane possesses abundant amino groups on the surface, contributing to its ultrahigh adsorption capacity of more than 1800 mg g −1 and rapid adsorption rate with concentrations ranging from 20 to 100 mg L −1 for organic dye, Direct Red 23.…”
Section: The Adsorption Of Heavy Metals and Organic Dyesmentioning
confidence: 99%
“…The electrospinnun polymer nanofiber membranes have a high aspect ratio and surface adsorption energy, providing an effective adsorbent material that can be regenerated without secondary contamination [ 230 , 231 , 232 , 233 ]. Recently, Zhao et al reported a simple strategy to fabricate amine-functionalized ultrathin polyacrylonitrile nanofiber of 100 nm diameter using a mixed solution electrospinning procedure, to efficiently remove organic dyes from aqueous media [ 234 ]. The ultrathin polyacrylonitrile nanofiber membrane possesses abundant amino groups on the surface, contributing to its ultrahigh adsorption capacity of more than 1800 mg g −1 and rapid adsorption rate with concentrations ranging from 20 to 100 mg L −1 for organic dye, Direct Red 23.…”
Section: The Adsorption Of Heavy Metals and Organic Dyesmentioning
confidence: 99%
“…With the development of technology and the large demand for textiles and printing, the industrial discharge is gradually increasing. These industrial wastewaters are highly variable and complex, which can contain suspended particles and refractory organic substances such as dyes. The complexity and variability of these wastewaters makes most commonly adopted single-step technologies fail to meet stringent waster regulations. To achieve complete removal of these pollutants, wastewater treatment facilities have to adopt a series of complicated processes that combine different technologies of adsorption, oxidation, , disinfection, and filtration. Therefore, given the rapidly expanding inventory of industrial wastewaters and increasing demands for high treatment efficiency for these complex wastewaters, it is urgent to find a viable and simple strategy to realize complete remediation of these pollutants from wastewater through a single-step treatment.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 These complicated components of industrial wastewater can harm organisms through ingestion or accumulation, causing great physiological abnormalities. 11,12 Therefore, it is of vital importance to fabricate a modified method for emerging wastewater hazards. 13…”
Section: Introductionmentioning
confidence: 99%